The genus Aphelocheirus Westwood, 1833 (Hemiptera: Aphelocheiridae) in the Iberian Peninsula - Carbonell, José Antonio; Abellán, Pedro; Arribas, Paula; Elder, Jean François; Millán, Andrés (Zootaxa, 2011)
This study updates current knowledge of the relationships and geographical distributions of the species from the genus Aphelocheirus in the Iberian Peninsula which, until now, have been involved in nomenclatural and taxonomic confusion. The morphological and molecular analyses presented in this study confirm the taxonomic validity of A. murcius and the absence of A. aestivalis in the Iberian Peninsula. The shape of the left paramere emerged as the only valid characteristic to differentiate both species. Specimens of Aphelocheirus from northern Spain, previously identified as A. murcius, formed an independent lineage genetically distinct to A. murcius and A. aestivalis, although morphologically indistinguishable from A. murcius.